Strain estimation of CFRP-confined concrete columns using energy approach - Pham, Thong; Hadi, M. (ASCE-AMER SOC CIVIL ENGINEERS, 2013)
A new model is presented for calculating the axial strain of carbon fiber-reinforced polymer (CFRP)-confined concrete columns. An energy-balance approach is introduced to establish a relationship of the energy absorption between a confined concrete column and CFRP. The proposed model was verified using a large database collected from 167 CFRP-confined plain concrete specimens. This database contains 98 circular specimens with diameters ranging between 100 and 152 mm, and 69 square specimens having a side length ranging between 100 and 152 mm. The database covers unconfined concrete strengths from 20 to 50 MPa. The proposed model shows very good correlation with the experimental results. In addition, the proposed model also provides a comparative prediction of the strain of CFRP-confined concrete columns in two extreme cases, i.e., (1) insufficient confinement, and (2) heavy confinement, which are not usually well predicted by other models.